2017
DOI: 10.1007/s11605-017-3358-5
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cocoon Syndrome: a Rare Cause for Recurrent Abdominal Pain

Abstract: Abdominal cocoon syndrome, or sclerosing peritonitis, is a rare condition characterized by encasement of small bowel loops by a thick fibrous scar. It most commonly presents as nonspecific vague chronic abdominal pain and weight loss, and is difficult to recognize clinically until the patient develops symptoms of bowel obstruction. We present a case of abdominal cocoon syndrome in a 65-year-old female and describe its clinical, imaging, and pathologic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As a result, 97 articles were included in our study. [3–41] The flow diagram of the study is shown in Figure 4. These articles were carefully studied, and a database with the patients’ characteristics was made, which could be available if requested.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, 97 articles were included in our study. [3–41] The flow diagram of the study is shown in Figure 4. These articles were carefully studied, and a database with the patients’ characteristics was made, which could be available if requested.…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal cocoon is rare, and most cases are diagnosed during exploratory laparotomy. It often presents with unexplained abdominal pain, abdominal distension, or intestinal obstruction ( 8 10 ). Typical abdominal CT scans show that the bowel is twisted and folded in the shape of an accordion, or a banana surrounded by a layer of dense linear membrane, and the mesenteric and blood vessels are often involved, twisted, and deformed ( 6 , 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal cocoon is more common in men, and the ratio of male to female is about 1.2-2:1 (5,6). Abdominal cocoon is a rare peritoneal disease that was first reported and named by Foo et al It is characterized by small intestinal obstruction caused by all or part of the small intestine covered by a dense fibrous membrane, also known as idiopathic sclerosing peritonitis, small intestinal incarceration, and small intestinal fibrous membrane entrapment (7,8).…”
Section: Discussionmentioning
confidence: 99%